Case Report: Bilateral testicular teratoma in an infant with torsion of an intra-abdominal testis and contralateral testicular teratoma - Hua, Chaoyang; Fan, Hongjie; Guo, Zhan; Li, Xing; Yang, Yanfang; Bi, Jianpeng (Frontiers in Pediatrics, 2025)
BackgroundBilateral testicular tumors in infants are extremely rare. This case report describes synchronous bilateral mature teratomas complicated by torsion of an intra-abdominal undescended testis (IAT), and underscores the clinical importance of early diagnosis, timely surgical intervention, and fertility-preserving management, providing valuable reference for future cases.Case presentationA 3-month-old boy presented with an empty right hemiscrotum. Imaging revealed a right intra-abdominal mass (22.8 × 15.9 × 21.3 mm) and left testicular lesion (7.1 × 3.9 × 7.0 mm). Serum alpha-fetoprotein was within normal limits for age, suggesting benign disease. Laparoscopy confirmed a torsed necrotic right testicular mass, managed by orchiectomy. Left testis-sparing surgery excised a separate tumor. Histopathology confirmed bilateral mature teratoma. Hormonal profiles, including testosterone (0.81 ng/mL) and follicle-stimulating hormone (3.74 mIU/mL), as well as karyotype (46,XY), were normal. No additional therapy was required, as mature teratomas are benign. Postoperative alpha-fetoprotein levels normalized, with no recurrence at 6-month follow-up. Parental education regarding testicular examination is important for early detection of future abnormalities.ConclusionsTumors associated with intra-abdominal undescended testes warrant urgent intervention due to torsion risk. Surgery preserving testicular tissue is recommended for bilateral benign teratomas to maintain fertility. Serial alpha-fetoprotein monitoring and ultrasound surveillance are essential postoperatively.